(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
This community service project aims to train Sunday school teachers at GMIM Bethel Winangun to create digital teaching aids. The training addresses the need for teachers to adapt to digital advancements and enhance their multimedia teaching skills. The project involved interactive lectures and practical sessions, resulting in improved teaching methods and engagement with children. The training sessions were conducted in July 2023, covering topics such as AI tools for curriculum planning and creating presentations with AI. The outcomes include the development of digital teaching aids and increased creativity and digital literacy among teachers.